Political business cycles in local employment : evidence from Portugal - Coelho, César (2006)
Using employment data for Portuguese municipalities, we find strong evidence of political business cycles. Employment increases shortly before elections mainly in municipalities where the mayor’s party has a majority of deputies in the municipal assembly and where she is running for reelection.